GERMINAÇÃO DE SEMENTES DE ESPÉCIES FLORESTAIS COLETADAS NO MUNICÍPIO DE ROQUE GONZALEZ – RS - Silva, Felipe A. d. N. e.; Klein, Fatima R. S.; Portella, Gabrieli Z.; Saturno, Camila; Franco, Elci T. H. (Salão do Conhecimento, 2013)
Resumo